In Echtzeit : das Jahr 1938 aus jüdischer Perspektive = Posts from the past : 1938 from a Jewish perspective - Bistrović, Miriam 1981- HerausgeberIn; Mecklenburg, Frank HerausgeberIn; Weitzer, William H. HerausgeberIn; Wrobel Bloom, Magdalena M. HerausgeberIn; Brown, David ÜbersetzerIn; Schmutzler, Barbara Ann ÜbersetzerIn; Leo Baeck Institute (Schriftenreihe / Bundeszentrale für Politische Bildung, 2020)
Catalog of an online exhibition entitled 1938 Projekt (1938 Projekt or Project), in which the Leo Baeck Institute published daily entries based on archival documents from the year 1938, revealing 365 personal stories by the end of the year. These stories provided personal narratives describing the impact of the Nazi regime on the Jews of Germany and Austria